Propagation of infantile gastroenteritis virus (orbi-group) in conventional and germfree piglets. - Middleton, P J (1975)
Infantile gastroenteritis virus (orbi-group) recovered from stools of infants with acute nonbacterial gastroenteritis was administered per os to germfree and conventional piglets. Virus was found subsequently in stools and in the mucosal epithelial cells of the small intestine of these animals. Some animals developed diarrhea. Added proof of orbivirus replication was obtained through the use of tritiated uridine injections and the recovery of labeled virus in gut contents at the time of autopsy. Serological conversion was demonstrated in infected germfree piglets.